Development of Phonics Method through Magic Board to Stimulate Reading Skill of Children Aged 5 – 6 Years - Humaeroh, Dini; Suryani, Yuni Dwi (Journal of English Language and Education, 2025)
This research aims to develop a phonics-based learning method using a "Magic Board" to stimulate reading abilities in children aged 5–6 years at Kindergarten A Grace. The study adopts the Rowntree development model, which includes the stages of planning, development, and evaluation, and is tested using Tessmer’s formative evaluation approach. This includes self-evaluation, expert review, one-to-one evaluation, and small group evaluation. Data were collected through observation, interviews, and documentation. The validation results from expert judgment indicated that the media aspect achieved a score of 90%, while the material aspect scored 97%, demonstrating high validity. In the one-to-one evaluation involving three children, the effectiveness reached 92%, while the small group evaluation with nine children yielded a practicality score of 93%, resulting in an average practicality of 92% (categorized as very practical). The development of the Magic Board media for children aged 5–6 years at Kindergarten A Grace is therefore proven to be highly valid and practical. These findings are supported by the strong alignment between the media content and the characteristics of young learners, as well as its relevance to the curriculum in use. The media development process involved several key stages, from initial prototype design and expert review to child-centered evaluations using Tessmer’s formative assessment. Each step yielded positive results, supporting the effectiveness of the Magic Board as a learning tool in early childhood education.